Molecular docking, Synthesis and Characterization of New Indomethacin and Mefenamic Acid Analogues as Potential Anti-inflammatory Agents - Mustafa Taha Abdull; Monther F. Mahdi; Ayad k. Khan (College of Pharmacy / Mustansiriyah University, 2023)
In this work the pharmacological study and synthesis of new thiadiazine bearing on triazole which obtained from hippuric acid ,  indomethacin and mefenamic acid that have carboxylic acid moiety, Drugs with carboxylic groups and thiocarbohydrazide interacted to produce the 4-amino-5-aryl-4H-1,2,4-triazole-3-thiol (1a-c). and the starting products 4-amino-5-aryl-4H-1,2,4-triazole-3-thiol) were treated with chloroacetyl chloride to produce final products (2a-c). To confirm the structure of the generated compounds, FT-IR, 1H-NMR, and mass spectroscopy were used to characterize all derivatives (intermediate and final products). The in vivo anti-inflammatory efficacy of some derivatives and thier toxicity to animals (in vivo) were evaluated. And then derivatives were subjected to molecular docking to create safe and efficient molecules. To test each derivative's ability to bind to the enzyme's active site, it was docked into the active sites. To determine the synthetic compound's topological polar surface area, bioavailability, and drug-likeness, An investigation of absorption, distribution, metabolism and elimination was performed. According to the findings, the tested derivatives adhered to the Lipinski rule and were ingested